1987
DOI: 10.1016/0304-3959(87)91072-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of injection pain in children

Abstract: Researchers have come to understand a great deal about pain mechanisms, especially in the past 30 years. This understanding has spawned the development of a number of psychological pain control strategies which have been extensively assessed for use with adults. Less is known about pain control strategies in children. The purpose of this study was to assess the value of 2 cognitive strategies (suggestion and music distraction) in reducing pain in children. Two hundred children, aged 4.5-6.5 years, receiving ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(91 citation statements)
references
References 13 publications
4
85
1
1
Order By: Relevance
“…The influence of earlier pain experience, but not the number of previous TU injections, is consistent with either that certain men are more prone to experience post-injection pain or that an earlier painful experience(s) with injection may sensitize or continue to influence subsequent post-injection pain experience. Similar observations supporting the latter mechanism are reported in wellcontrolled studies, mostly in children, showing that psychological techniques, such as distraction [28] and/ or topical local anaesthetic [29] or vapour coolant [30], significantly reduce IM injection pain and may prevent entrenching of long-term needle phobia [31,32]. The role played by expectation, with or without involving semivoluntary muscular tensing before subsequent injections, in this study remains speculative.…”
Section: Discussionsupporting
confidence: 88%
“…The influence of earlier pain experience, but not the number of previous TU injections, is consistent with either that certain men are more prone to experience post-injection pain or that an earlier painful experience(s) with injection may sensitize or continue to influence subsequent post-injection pain experience. Similar observations supporting the latter mechanism are reported in wellcontrolled studies, mostly in children, showing that psychological techniques, such as distraction [28] and/ or topical local anaesthetic [29] or vapour coolant [30], significantly reduce IM injection pain and may prevent entrenching of long-term needle phobia [31,32]. The role played by expectation, with or without involving semivoluntary muscular tensing before subsequent injections, in this study remains speculative.…”
Section: Discussionsupporting
confidence: 88%
“…A cycle of increased anxiety, fear, and pain can result from negative experiences with injections, which in turn can exacerbate future injection experiences. 21 Children with a history of negative medical experiences showed higher levels of anxiety before a venipuncture procedure, and were more distressed and less cooperative during the procedure. 22,23 The present study also showed that those children who had previous hospitalization more than five days depicted increased sign of perception of pain at initiation, at five minute and at termination of administration of intravenous injection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have examined changes in chiidren's pain expression over time. Such studies consistently find that older children show less pain-related behavior (Blount et al, 199 1;Craig et al, 1984;Dahlquist et al, 1995;Dahlquist et al, 1994;Fowler-Kerry & Lander, 1987;Gonzaiez et al, 1989;Jacobsen et al, 1990;Manne, Bakeman, Jacobsen, & Redd, 1993) and more coping (Manne et ai., 1993) (Kopp, 1982), which allows them to better notice their parents' general behavior patterns, and their responses to pain in particular. Their mernories also improve (Kopp, 1982), allowing them to better recall past patterns of interaction surrounding pain.…”
Section: Aternal S E N S I T~t V and Chid Paiqmentioning
confidence: 96%